FE-based simulation and validation of a pedestrian impact detection system - Zeng, Hanying (My University, 2025)
According to the European Commission, pedestrians accounted for 18.4% of road traffic fatalities in the EU in 2023 [5]. Modern vehicles integrate systems such as the Active Hood Lift System (AHLS), which lifts the bonnet to reduce head trauma during pedestrian collisions[3]. A key component enabling AHLS is the pressuresensitive sensor tube, which detects frontal impacts and triggers hood deployment within milliseconds. To support the deployment of AHLS, this project aimed to develop and validate a Finite Element (FE) model of an air-filled pressure sensor tube for use in pedestrian impact detection. The model was implemented in LSDYNA and evaluated against physical impact tests conducted at three velocities. Waveform correlation between simulated and measured pressure signals was assessed using the Waveform Index Factor (WIFac) to quantify model accuracy. The model was assessed under varying configurations to evaluate its predictive accuracy. Foam material properties and fixation methods were systematically tested. Among them, the calibrated foam material model generally yielded the highest waveform correlation with physical test results, achieving WIFac values typically above 70% across the tested velocities. By contrast, plastic strap fixation and alternative foam models resulted in lower WIFac values, often below 60%. A nonlinear inverse relationship was observed between the tube’s Young’s modulus and the resulting peak pressure, with 0.001 GPa providing the closest match for the advanced dynamic test. This is physically consistent, as lower stiffness allows for greater deformation and a more gradual pressure increase. Sensitivity analysis was performed by introducing small perturbations in initial velocity and impactor position to evaluate the model’s robustness. Results showed that the waveform structure remained stable under moderate variations, supporting the model’s reliability within expected test tolerances. Therefore, the calibrated foam model is recommended as the reference configuration for simulation-based evaluations of AHLS pressure tube systems. To explore the model’s applicability in more complex scenarios, additional simulations were conducted using the PDI-2 full-leg impactor. These simulations exhibited increased signal deviations, indicating that further refinement is necessary for integration into biomechanical assemblies. Future work should focus on experimental validation of material parameters and extension to full-vehicle implementations.
Keywords: FE; FEM; Pressure tube; AHLS; WIFac; PDI-2